Forgiveness in Ecumenical Dialogue: Reflections of a Not Indifferent Christian - Wacław Hryniewicz (Nicolaus Copernicus University in Toruń, 2016)
The article shows a difficult task the forgiveness of historical sins has to accomplish in the ecumenical dialogue in order to create a new space for reconciliation between Churches and religions. This can be done only when human efforts are "fostered by the grace of the Holy Spirit" (Decree on Ecumenism, par. 1). Openness and sensitivity are therefore required to His transforming action in the Church. There are many obstacles on the road leading to achieve mutual forgiveness and reconciliation. The process of the healing of memories does not imply a subconscious suppression of painful recollections of humiliations and harms caused to other believers in the history of Christianity. The most dramatic events of the past demand an open exchange of views on what has been often passed over in silence, so that a deep purification, a truly evangelical katharsis of memory and lasting reconciliation are eventually achieved. Without mutual confidence and forgiveness there is no future for ecumenism. The new millennium demands from Christians not to remain imprisoned by the memory of the past. Hope and confidence are grounded in the very fact that the Churches slowly learn in dialogue to see each other with long-sightedness of sincere forgiveness.